Learning and Mastering English Speaking Skills by Using Premium Speaking Cards for Adult Learners - Ali Amran (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This study is aim to demonstrate how attractive and interesting it is to leam English by using “Premium SpeakingCards”. Since English has become a global language, so there are huge number of people worldwide tend toacquire it. One strange statement is that “Do not study the language but speak with the language”. Then criticsarise, how can a learner speak a language without having any talent? One can say anything in a certain language,but the question is do the language experts understand what he is saying? In fact that there are huge number ofteaching methods that teachers can apply, but how effective, interesting it is and how long it will take the learnersto acquire it. Effective strategies serve to regulate emotions, motivation, and attitudes e. g. strategies for reductionof anxiety and for self-encouragement. And the last is that strategy is called social strategies which include theactions which learners choose to take in order to interact with other learners with proﬁcient second -languagespeakers (Willy and George M Jacobs, 1998; p.6.). The researcher found that this Premium Speaking Cards canencourage the learners become more active, more creative and more aggressive in developing and delivering theirspeaking skills and they become more active in possessing English as a foreign language. This is the reason whythis Premium Speaking Cards must be conducted so both teachers and leamers can be more active, more creativeand more constructive, more productive in learning and mastering English.Keywords - mastering; active; creative; aggressive; premium speaking cards